2018
DOI: 10.1038/s41593-018-0096-2
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Altered cerebellar connectivity in autism and cerebellar-mediated rescue of autism-related behaviors in mice

Abstract: In the version of this article initially published, the Simons Foundation was missing from the list of sources of support to P.T.T. in the Acknowledgments. The error has been corrected in the HTML and PDF versions of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Therefore, low‐frequency force oscillations may be associated with low‐frequency fluctuations of activity in visuomotor brain regions activated during grip‐force tracking. Right Crus I and left IPL are interconnected brain areas activated during precision‐grip force tracking [Neely et al, 2013; Vaillancourt et al, 2006] and are implicated in core ASD social and communication deficits [Stoodley et al, 2018]. Future studies should examine whether the low frequency oscillations (<0.25 Hz) observed during visuomotor force tracking are associated with anomalous connectivity within the visuomotor network, including right Crus I and left IPL, in children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, low‐frequency force oscillations may be associated with low‐frequency fluctuations of activity in visuomotor brain regions activated during grip‐force tracking. Right Crus I and left IPL are interconnected brain areas activated during precision‐grip force tracking [Neely et al, 2013; Vaillancourt et al, 2006] and are implicated in core ASD social and communication deficits [Stoodley et al, 2018]. Future studies should examine whether the low frequency oscillations (<0.25 Hz) observed during visuomotor force tracking are associated with anomalous connectivity within the visuomotor network, including right Crus I and left IPL, in children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…4a). Using a combination of recently developed technologies such as optogenetics, chemogenetics, trans-synaptic tracers and single-cell sequencing in both animal models and human cells [76][77][78][79] , we now have the ability to determine the effect of genetic variants on specific cells and networks with unprecedented detail.…”
Section: Identifying the Circuitsmentioning
confidence: 99%
“…In addition to epilepsy and complications to tuber formation throughout the body, approximately 50% of TSC patients meet the criteria for diagnosis of ASD, with a substantial portion of others suffering more subtle neuropsychiatric disturbances (Sundberg and Sahin, 2015; Gipson and Johnston, 2017). Though a previous study linked cerebellar tuber formation to the development of ASD (Weber et al, 2000), more recent efforts have been made to investigate how Purkinje cell function is specifically disrupted through targeted knock-out of TSC1 in Purkinje cells (Tsai et al, 2012; Stoodley et al, 2018). Initial analysis showed that when TSC1 is knocked out of Purkinje cells, there are substantial morphological and neurophysiological changes in Purkinje cells (Tsai et al, 2012).…”
Section: Mouse Models Of Cerebellar Cognitive Disordersmentioning
confidence: 99%
“…These changes were sufficient to cause behavioral anomalies consistent with what is observed in patients with ASD, including aberrant social interactions, increased repetitive behaviors, and changes in vocalizations (Tsai et al, 2012). Subsequent studies showed that genetically altering TSC1 in vivo also induced structural connectivity defects within cortical areas that have been suspected to be dysfunctional in patients with ASD (Stoodley et al, 2018). These studies were among the first to mechanistically link Purkinje cell dysfunction with specific neurobehavioral outcomes in ASD and support the interesting hypothesis that dysfunction in cerebellar computations, that are perhaps localized to specific lobules such as right CrusI/II, could lead to motor as well as cognitive dysfunction.…”
Section: Mouse Models Of Cerebellar Cognitive Disordersmentioning
confidence: 99%